(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Solar greenhouse drying is useful in conserving energy utilizing natural source of energy from sun and to speed up the process of drying crops. The main problem with unsold crops with farmers is addressed by solar drying and preserving. In this case study, a large scale solar greenhouse dryer for banana is studied. The dryer was installed at Thottiyam, Tiruchirapalli, Tamil Nadu, in India. The floor area of parabolic dryer is 6.1 m x 8.4 m. Because of protected drying environment, a good quality dried banana is obtained free from dirt and pests. Bananas each of approximately 50 g mass are dried in two days in this location